A metagenomic-based, cross-seasonal picture of fungal consortia associated with Italian soils subjected to different agricultural managements. (December 2017) - Panelli, Simona; Capelli, Enrica; Comandatore, Francesco; Landinez-Torres, Angela; Granata, Mirko Umberto; Tosi, Solveig; Picco, Anna Maria
Abstract: This work pictures the biodiversity of fungal consortia inhabiting real agroecosystems, sampled in one production farm in two seasons (spring, autumn), coinciding with climate gradients and key moments of the agricultural cycle. Soil was sampled from three plots differently managed in terms of fertilization, pesticide and tillage application: conventional, organic, no-tillage. Metagenomic analyses on ITS1 amplicons depicted the highest indexes of richness for organic. No-tillage resulted in inhabitation by the most divergent communities, with their own composition, prevalence and seasonal trends. Ascomycota always predominated, with the exception of conventional, that had high abundance of a single basidiomycete species. Our results showed evidence that agricultural soils under organic and no-tillage systems harbour distinct mycobiota, even in neighbouring fields. From our results, fungal consortia altered even in the first year after the management change.